Valorization of (Bio)Ethanol over MoO3/(WO3-ZrO2) Sol-Gel-like Catalysts - Ana Paula Soares Dias; Bruna Rijo; Manuel Francisco Costa Pereira; Rodica Zăvoianu; Octavian Dumitru Pavel (Reactions, 2024)
Bioethanol, which is currently produced commercially from a growing variety of renewable biomass and waste sources, is an appealing feedstock for the production of fuels and chemicals. The literature clearly shows that bioethanol is a versatile building block to be used in biorefineries. The ethanol conversion using several catalysts with acidic, basic, and redox characteristics results in a diverse assortment of high-value bioproducts. High-acidity tungsten zirconia-based catalysts are stated to compete with traditional zeolitic catalysts and can be employed in the dehydration of ethanol to ethylene, but for a low reaction temperature acetic acid is formed, which causes corrosion issues. WO3-ZrO2 (W/Zr = 1, atomic) catalysts modified with MoO3 were prepared by a sol-gel-like procedure and tested in a gas phase ethanol conversion in the presence of air. The citrate derived xerogels were annealed at 853 K for 12 h, allowing low surface area (<10 m2/g) materials with a Mo-W mixed-oxide-rich surface over tetragonal nanostructured zirconia. Catalysts with MoO3-loading produced mainly acetaldehyde, instead of ethylene, as a result of the high reducibility of Mo6+ when compared to W6+. During the reaction, the Mo6+ becomes partially reduced, but Mo6+/Mo5+ species are still active for methanol conversion with increased ethylene selectivity due to the high acidity of tetrahedral MOX species formed during the reaction. Adding water to ethanol, to simulate bioethanol, only leads to a slight inhibition in ethanol conversion over the MoO3/(WO3-ZrO2) catalysts. The results show that molybdenum oxide deposited on tungstated zirconia catalyst is active, with low sensitivity to water, for the valorization of bioethanol into high-value chemicals, such as ethylene and acetaldehyde, and whose selectivity can be tuned by changing the amount of MoO3 that is loaded. The MoO3/(WO3-ZrO2) catalysts prepared show catalytic behavior similar to that of noble metal-based catalysts reported in the literature for the dehydrogenation of bioethanol in high-value chemicals.